1990
DOI: 10.1118/1.596553
|View full text |Cite
|
Sign up to set email alerts
|

Validity of transition‐zone dosimetry at high atomic number interfaces in megavoltage photon beams

Abstract: Measurement of dose or dose perturbation factors at high atomic number interfaces are usually performed with a thin-window parallel-plate ion chamber. In a transition region, under nonequilibrium conditions, accuracy of ion chamber readings for the dose measurements has often been questioned. This paper critically analyzes the factors (stopping power ratio and charge collection) for the dose measurements at interfaces. Monte Carlo simulations were performed to investigate the secondary electron spectrum produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…It has long been known that when metal inhomogeneities with high atomic numbers are in the path of photons or electron beams, the dose distribution is altered and regions of overdosage or underdosage are produced. [14][15][16][17][18] Molecules with similar atomic numbers have nearly the same dose distribution. Accordingly, titanium (which is atomic number 22) and HAP, which has calcium (atomic number 20) as a primary component of its structure, have nearly the same dose distribution.…”
Section: Discussionmentioning
confidence: 87%
“…It has long been known that when metal inhomogeneities with high atomic numbers are in the path of photons or electron beams, the dose distribution is altered and regions of overdosage or underdosage are produced. [14][15][16][17][18] Molecules with similar atomic numbers have nearly the same dose distribution. Accordingly, titanium (which is atomic number 22) and HAP, which has calcium (atomic number 20) as a primary component of its structure, have nearly the same dose distribution.…”
Section: Discussionmentioning
confidence: 87%
“…Das and colleagues measured dose perturbation factors (DPFs) proximal and distal for simulated bone-tissue interface regions using a parallel plate chamber for both 6 and 24 MV X-ray beams (Das et al 1990;Das and Khan 1989). They reported DPFs of 1.1 for the 6 MV beam and 1.07 for the 24 MV beam at the proximal interface.…”
Section: Dose-bone Interfacesmentioning
confidence: 97%
“…Das and associates measured forward dose perturbation factors (FDPFs) following a 10.5 mm thick stainlesssteel layer simulating a hip prosthesis geometry (Das et al 1990). They measured a dose enhancement of 19% for 24 MV photons, but only 3% for 6 MV photons.…”
Section: Dose-prostheses (Steel and Silicon)mentioning
confidence: 99%
“…There was a difference (-2.5%) between measurement and calculated dose. The CCC algorithm predicts a dose near to inhomogeneity exactly (25)(26)(27)(28). The CCC algorithm as used for the Monte Carlo calculation method and the results show that it has an accuracy of 1% in complex geometries (29).…”
Section: Tps Dose Calculation Algorithmsmentioning
confidence: 99%
“…Linthout et al showed the three different calculation algorithms (Clarkson, PB and the Collapsed Cone (CC) algorithms) overestimate the dose in the PTV at the boundary with the low-density tissue, with 12, 10 and 7% for the Clarkson, the PB and the CC algorithm, respectively (24). In another study, Das et al showed that the Collapsed cone algorithm has better accuracy than the PB algorithm in the interface of inhomogeneous media (27). Nisbet et al showed Collapsed cone has better accuracy than the PB model in interface lung/tissue and Collapsed cone and the PB model also have inadequate accuracy in interface bone/tissue (25).…”
Section: Tps Dose Calculation Algorithmsmentioning
confidence: 99%